If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = m + -2 Reorder the terms: 2 = -2 + m Solving 2 = -2 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 2 + -1m = -2 + m + -1m Combine like terms: m + -1m = 0 2 + -1m = -2 + 0 2 + -1m = -2 Add '-2' to each side of the equation. 2 + -2 + -1m = -2 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = -2 + -2 -1m = -2 + -2 Combine like terms: -2 + -2 = -4 -1m = -4 Divide each side by '-1'. m = 4 Simplifying m = 4
| 2+3x=6x+32 | | -9+2x+x=15 | | 5(x-4)+2=13 | | (2x+16xy)dx+(8x^2-30y^2)dy=0 | | 5x+4x-32=31 | | 5w=9.9+4.8+8w | | 3x-77+6x=40 | | -x+1=2x-32 | | -31+3x+6x=68 | | 12.50x=1.95x+125 | | -10-2x+5x=11 | | 7x+9=21+3x | | 5w+14=2(5y+6) | | 5x+4x-94=32 | | K-12=6+(-12) | | -4v^2-7v=-57 | | 5x+4x-94=33 | | -2+x=-4x+33 | | 6x-21-2x=23 | | -(q+14)=(-3)+(-14) | | -5x-5=3x-53 | | 4x-5+-6=12 | | 5p^2-4p-1=0 | | 2+x=7x-52 | | -70=5x+5x-10 | | -7x+9-3x=27 | | 33=2x+7x+6 | | 5d-7=8d+2 | | -12+4x-2x=10 | | 7b=11 | | -4x-5-x=-5 | | 2x+3x-1=4 |